Writing history in time of war : Michael Rostovtzeff, Elias Bickerman and the "Hellenization of Asia" - Manning, Joseph Gilbert; Bickerman, E. J. (Elias Joseph), 1897-1981; Rostovtzeff, Michael Ivanovitch, 1870-1952 (Stuttgart : Franz Steiner Verlag, 2015)
"This book is about two giants of 20th century historiography, Michael Rostovtzeff (1870-1952) and Elias Bickerman (1897-1981) whose lives and careers intersected on many occasions but who have rarely been discussed together. 'Writing History in Time of War' contains, in the main, the results of a lecture given by Pierre Briant and a series of responses to that lecture as the Fourth Annual Michael I. Rostovtzeff Lecture and Colloquium hosted by the Department of Classics at Yale University. Both--Rostovtzeff and Bickerman--were deeply affected by war and exile, and both sought relevance for the modern world in their work and read their own experiences back into their interpretations of the ancient world. This volume adds much new and exciting information about these two scholars, and brings into focus how their own life experiences informed their historical interpretation of the Hellenistic world. Even those who are well familiar with them will find much of value in this volume"-- ‡c Back cover.
Michael Rostovtzeff and Elias Bickerman in context / J. G. Manning -- Michael Rostovtzeff, Elias Bickerman and the "Hellenization of Asia" : from Alexander the Great to World War II / Pierre Briant -- The Europeanisation of the classical east : à propos of the book by Michael Rostovtzeff / Elias Bickerman, trans. Amélie Kuhrt -- Three personal relflections on Elias Bickerman / Matthew W. Stolper -- The cosmopolitan Jew and the allure of Zion : Elias Bickerman between European secularism and Jewish particularism / John Collins -- The multiple identities of Elias Bickerman / Mac Domingo Gygax -- Rostovtzeff and Bickerman on Hellenization : a comparison and contrast / Albert Baumgarten -- Appendix A. Adventures of a college professor / M. I. Rostovtzeff -- Appendix B. The academic career of Professor M. I. Rostovtzeff, Yale University.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Bickerman, E. J. -- 1897-1981.; Rostovtzeff, Michael Ivanovitch, -- 1870-1952.; Bickerman, E. J. -- 1897-1981; Rostovtzeff, Michael Ivanovitch, -- 1870-1952; Historians; Historians